Without an equality sign and not knowing the plus or minus values the information given can't be considered to be an equation.
There is no such pair. The solution to equation 1 and equation 2 is x = 1, y = 1. The solution to equation 2 and equation 3 is x = 1, y = 1. And the solution to equation 1 and equation 3 is any point on the line 3x + 2y = 5 - an infinite number of solutions. The fact that the determinant for equations 1 and 3 is zero (or that they are not independent) does not mean that there is no solution. It means that there is no UNIQUE solution. In this particular case, the two equations are equivalent and so have an infinite number of solutions.
It is also x = 5 8zx + 5 = 2j + 3 → 8zx + 2 = 2j → 4zx + 1 = j Which is the first equation, which has a solution x = 5.
-2
10 (-2) 5 (-4)
Without an equality sign it is not an equation but if you mean: 5x=2 then x=2/5 or 0.4
It is [1 + sqrt(5)]/2 It is the solution to the equation 1/x = x/(1+x)
I understand the equation to be y = -3x - 2 and the point to be (5,1). I substitute 1 for each appearance of y and 5 for each appearance of x: 1 = -3(5) - 2 = -15 - 2 = -17, which is not a true statement. Therefore, that is not a solution. To get a solution, set x=1, and calculate y by substituting this value (1) for x wherever it appears: y = -3(1) - 2 = -3 - 2 = -5. Therefore, (-5,1) is a solution. (I suspect that this is what you meant to put in the question.)
There is one solution. To find it, divide both sides of the equation by 2. This leaves you with x=5, where 5 is your solution.
On the list that accompanies the question, there is no equation with that solution.
An equation may have zero, one, or more solutions (this is also true for a system of equations). The equation 2 + x = 5 has only solution, for example. x can only equal 3, so there is one solution. (An example of an equation with more that one solution is x2 = 4. In this case x can equal 2 or -2, so this equation has two solutions. An example of an equation with an infinite number of solutions is x + 6 = 3*2 + x. x can equal any number to make this equation true, so it has an infinite number of solutions. The equation x = x + 1 is an example of an equation with no solutions.)
(2, 3) is a solution only if it satisfies the equation. x + 5y = 4 (2) + 5(3) =? 4 2 + 15 =? 4 17 = 4 False Therefore, (2, 3) is not a solution to the given equation.
x - 3 = √(5 - x); square both sides, for the left side use (a - b)2 = a2 - 2ab + b2 x2 - 6x + 9 = 5 - x; add x and subtract 5 to both sides x2 - 5x + 4 = 0; this is factorable since 4 = (-1)(-4) and (-1) + (-4) = -5 (x - 1)(x - 4) = 0; let each factor equal to zero x - 1 = 0; x = 1 x - 4 = 0; x = 4 Check if 1 and 4 are solutions to the original equation. 1 - 3 =? √(5 - 1) -2 =? √4 (recall the radical symbol is looking only for the positive root) -2 = 2 false, so that 1 does not satisfy the original equation, so it is an extraneous solution. 4 - 3 =? √(5 - 4) 1 =? √1 1 = 1 true, so that 4 is a solution to x - 3 = √(5 - x).
x - y = 2 : Equation 1 2x + 3y = 4 : Equation 2 Multiplying Equation 1 by 3 gives 3x - 3y = 6 : Equation 3 Adding Equation 2 to Equation 3 gives 5x = 10 Dividing both sides by 5 gives x = 5 Substituting x=5 into Equation 1 gives 5 - y = 2 Therefore y = 3. Our final answer is therefore x=5 and y=3
It is a simultaneous equation and its solution is x = -1 and y = -5
A linear equation in one variable. Case 1: A conditional equation: True only for a value of the variable. Ex. x + 2 = 3, True only when x is 1. Case 2: Identity Equation: Always true. Ex. x + 2 = x + 2, True for any value of x. Case 3: x + 1 = x + 5, False for any value of x. We call a solution any value of the variable that satisfies the equation, meaning if we replace the variable with that value, the equation becomes a true statement. Example: -2(x -3) = 8 - 2x -2x + 6 = 8 - 2x (add 2x and subtract 6 to both sides) 0 = 2 False. Since this equation, which is equivalent to the original equation, is false, then the original equation is also false. Meaning, there is no real number for x that could satisfy the equation. So there is no solution to the equation.
The quadratic equation can be used to find the solution to any polynomial equation of the form a*(x^2) + b*x+c = 0. The roots are (-b (+/-) sqrt(b^2 - (4*a*c)))/2a. In this case, assuming the equation was supposed to read (x^2) + 5x - 6, the solutions are (-5 (+/-) sqrt (5^2 - (4*1*-6))/2 (-5 (+/-) sqrt (25 - (-24))/2 (-5 (+/-) sqrt (25 + 24))/2 (-5 (+/-) sqrt (49))/2 (-5 (+/-) 7)/2 (-5 + 7)/2 and (-5-7)/2 1 and -6. Or, one can factor the original formula into (x-1)(x+6) = 0, which makes it clear that 1 and -6 are the answers to this problem. More complex quadratics are harder to factor, but the quadratic formula always works.
Points: (0. 5) and (2, 3) Slope: -1 Equation: y = -x+5